Facile preparation of carbon quantum dots from biochar via microwave–assisted hydrothermal synthesis - Kamarol Zaman, Alif Syafiq (2019)
Carbon quantum dots (CQD) were successfully synthesized using microwave-assisted hydrothermal method using empty fruit bunch (EFB) biochar as the carbon precursor. Effect of temperature (60°C – 130°C), solvent concentration (0.1- 0.5 mole fraction of IPA) and reaction time (5 – 30 minutes) were investigated on CQD yield (%). The optimum process gives the highest yield and it is about 15.22% at 100°C with 0.1 mole fraction and in just 5 minutes. Material characterisations confirm the formation of CQD where microscopy images showed an average size distribution of 4.5 nm. Chemical structure has shown the presence of oxygenic functional groups such as hydroxyl, carbonyl/carboxyl at 3270 cm-1 and 1640 cm-1 respectively. The presence of these oxygenic functional groups are also supported by X-ray Photoelectron Spectroscopy analysis where C–C/C=C (284.6 eV), C-O (285.5 eV), C=O (286.5 eV) and COOH (288.1 eV). To complement experimental data, density functional theory (DFT) calculations were carried out at 6-31G(d) basis set and a comparison of three exchange correlation functions such as B3LYP, CAM-B3LYP and wB97XD. These functionals are able to calculate the ground state molecular structure of CQD where the subsequent frequency analyses for each functionals give no imaginary frequencies. The highest occupied molecular orbital and lowest unoccupied molecular orbital (HOMO-LUMO) gap obtained from 6– 31G(d) with Becke’s three parameter with Lee–Yang–Parr (B3LYP) is 6.381 eV and is closer to experimental band gap of 3.2 eV compared to Coulomb attenuating method with Becke’s three parameter with Lee– Yang–Parr (CAM–B3LYP) and wB97XD. In conclusion, a facile preparation of CQD from EFB biochar was successfully obtained from microwave-assisted hydrothermal process. The process was efficient, rapid, cost-effective and eco-friendly.